Role of Soluble FMS-Like Tyrosine Kinase (SFLT-1) /Placental Growth Factor (Plgf) Ratio as Prognostic Marker for Cases of Preeclampsia - Gasser M Elbishry; Ihab F Serag Eldin; Ahmed A ElShahawy; Gihan E Hawwary; Ahmed M Riad (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Objective: The aim of this study is to identify the role of sFlt-1/PIGF ratio as a prognostic marker for cases of preeclampsia.  Patients and methods: The current study is a case control study that was conducted over 90 cases of primigravida patients, 24-34 weeks of gestation, randomly selected patients from outpatient clinic and ER of Ain Shams Maternity Hospital, they were classified into two groups, first group is preeclampsia group which was 45 preeclamptic pregnancies (preeclampsia patients and cases with severe criteria) and the second group was control group which was 45 normal pregnancies. Each patient was examined by sFlt-1/ PlGF ratio immunoassay kits.  Results: In our study we have found that there was statistically significant positive correlation between the sFlt-1/PlGF ratio and blood pressure in 24-34 weeks. The correlations between the sFlt-1/ PlGF ratio and other laboratory markers were statistically significant as well. In the 24-34 weeks PE group, AST, ALT were positive meanwhile Platelet count yielded only a highly signifi cant negative correlation to the sFlt-1/PlGF ratio. We analyzed the time to delivery in all 45 patients with PE/HELLP within 2 days (24 patients), 2-7 days (10 patients), and later than 7 days (11 patients). Patients with interval to delivery within 2 days showed a higher sFlt-1/PlGF ratio, the sFlt-1/PlGF ratio in patients delivering within 2 days was (610.85). Patients with interval to delivery within 2-7 days exhibited a sFlt-1/PlGF ratio of (499.7). However, patients delivered later than 7 days had a sFlt-1/PlGF ratio of (230.43). For all PE/HELLP patients group (24-34 weeks), a sFlt-1/PlGF ratio greater than 590.1 (413.7 - 611.1) is associated with an 11.577 folds increased risk for an immediate occurence of delivery. The current study has found that the best cut off point after applying ROC curve between control group and cases group regarding soluble fms like tyrosine kinase/placental growth factor ratio was (> 85) which gave us sensitivity of 100%, specificity of 100% and accuracy of 100%. Conclusion: We concluded from our study that the important clinical implication for the use of the sFlt-1/PlGF ratio for diagnosis, differential diagnosis, and risk stratification in PE/HELLP patients. Patients with sFlt-1/PlGF ratio above the level of 85 were preeclamptic and should be monitered for upcoming complications, symptoms and signs of severity. It could be used as a prognostic tool regarding maternal and fetal outcomes for patients with Preeclampsia between 24-34 weeks of gestation and patients at risk of having PE.